Cleveland Clinic Socre – What is the Role of a Novel Prognostic Treadmil Score to Diagnose Coronary Artery Disease? (University Heart Journal, 2019)
Background: Ischemic heart disease is increasing all over the world even in the developing countries like Bangladesh. The incidence rate of coronary artery disease is escalating very rapidly among both male and female population in our country. Though exercise treadmill test (ETT) is a well accepted non-invasive investigation to diagnose Coronary Artery Disease (CAD), it has a high false positive and false negative result if ST segment response alone is calculated for interpretation of the test. Accuracy of different treadmill scores in our population is largely unknown. Clevelan Clinic Score is a prognostic ETT score which is validated for prognostic indication but may have some diagnostic value as well.Objective: To know the diagnostic role of Cleveland Clinic Score, currently which has only prognostic implication. Method: A Cross-Sectional study was carried out on patients attending University Cardiac Center in Bangabandhu Sheikh Mujib Medical University (BSMMU) for stable chest pain to find out the accuracy of Cleveland Clinic Scores (CCS) in comparison to other diagnostic treadmill scores namely Duke Treadmill Score (DTS) and Simple Treadmill Score (STS).Total 130 persons including male and female who have undergone ETT were included according to inclusion and exclusion criteria. Coronary angiogram reports were collected after the procedure was performed as per clinical practice. The accuracy of ST segment response & different treadmill scores were calculated and compared with each other.Result: ETT scores had better sensitivity and specificity than ST segment response which was affected by workup bias more. CCS, DTS and STS have 83.3% & 60.9%; 71.4% & 71.7%; 64.3% & 78.3% sensitivity & specificity, respectively. Receiver Operator Characteristics (ROC) curve analysis showed all of the three scores have similar area under curve (AUC) that means they have similar accuracy to diagnose CAD. But they have different sensitivity and specificity for different cut off value. Overall analysis showed accuracy of STS (83.9%) is comparable to that of DTS (83.3%), CCS (77%) .Conclusion: Among the three treadmill scores Cleveland Clinic Score has comparable predictive accuracy when compared with DTS, STS. Though a prognostic ETT score, CCS may have diagnostic role which need to be validated further.University Heart Journal Vol. 14, No. 2, Jul 2018; 62-66